2009
DOI: 10.1002/rcm.4250
|View full text |Cite
|
Sign up to set email alerts
|

Molecular depth profiling of multilayer structures of organic semiconductor materials by secondary ion mass spectrometry with large argon cluster ion beams

Abstract: In this study, we present molecular depth profiling of multilayer structures composed of organic semiconductor materials such as tris(8-hydroxyquinoline)aluminum (Alq3) and 4,4'-bis[N-(1-naphthyl)-N-phenylamino]biphenyl (NPD). Molecular ions produced from Alq3 and NPD were measured by linear-type time-of-flight (TOF) mass spectrometry under 5.5 keV Ar70) ion bombardment. The organic multilayer films were analyzed and etched with large Ar cluster ion beams, and the interfaces between the organic layers were cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 28 publications
1
79
0
Order By: Relevance
“…Using this approach, it was determined for DHB that a fluence of~0.7*10 12 Ar cluster ions/cm 2 is necessary to remove 1 nm of the crystal. This value is in the same range as those previously obtained for other organic systems such as leucine films [31] and the organic semiconductor material NPD [32]. Owing to the stronger shaped structure (Figure 1d), the drop in signal intensity is less precipitous for the analyzed HCCA crystal and the sputter rates that are obtained using the same approach as above for DHB will be less precise.…”
Section: Determination Of Sputter Ratessupporting
confidence: 82%
“…Using this approach, it was determined for DHB that a fluence of~0.7*10 12 Ar cluster ions/cm 2 is necessary to remove 1 nm of the crystal. This value is in the same range as those previously obtained for other organic systems such as leucine films [31] and the organic semiconductor material NPD [32]. Owing to the stronger shaped structure (Figure 1d), the drop in signal intensity is less precipitous for the analyzed HCCA crystal and the sputter rates that are obtained using the same approach as above for DHB will be less precise.…”
Section: Determination Of Sputter Ratessupporting
confidence: 82%
“…An increasing amount of literature demonstrates that polyatomic primary ions such as SF 5 + , C 60 + , and Ar n + are suitable for this purpose [1][2][3][4][5][6]. The total energy is shared by each atom in the cluster, limiting the penetration depth and thereby the extent of the chemically damaged layer under the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Gas-cluster-ion-beam (GCIB) composed of Ar atoms has become a popular ion source in time-of-ight secondary ion mass spectrometry (SIMS) since it has been shown that they allow collecting successful depth proles in several cases where smaller cluster projectiles have failed [1]. However, still not much is known about processes occurring during Ar cluster bombardment of organic materials.…”
Section: Introductionmentioning
confidence: 99%